Wearable technology metrics are associated with energy deficiency and psychological stress in elite swimmers - Lundstrom, E. A.; De Souza, M. J.; Koltun, K. J.; Strock, N. C. A.; Canil, H. N.; Williams, N. I. (International Journal of Sports Science & Coaching, 2024)
Energy deficiency (ED) and psychological stress affect athlete health. Given the emerging capabilities of wearable technology, the purpose of this study was to explore associations of wearable technology metrics in relation to lab-based measures of ED and psychological stress. We investigated the associations between (a) wearable-derived heart rate variability (HRV), resting heart rate (RHR), exercise strain and recovery, and (b) laboratory-derived measures of metabolism (resting metabolic rate (RMR), total triiodothyronine (TT3)) and a validated stress assessment (Recovery-Stress Questionnaire for Athletes (RESTQ)-52 items) in NCAA swimmers (n = 23, 10 male, 13 female) during heavy training. Swimmers were grouped by degree of metabolic adaption to ED using the ratio of actual-to-predicted RMR (utilizing the validated cutoff of <0.94) and by sex. Metabolically suppressed swimmers had lower HRV (81 ± 27 ms vs.110 ± 35 ms, p = 0.04). HRV correlated positively with RMR (kcal·kg LBM-1·day-1; where LBM stands for lean body mass) (r = 0.45; p = 0.03). HRV was negatively correlated with sport-specific (r = -0.46; p = 0.03) and total stress (r = -0.46; p = 0.03). In males, HRV correlated negatively with general stress (r = -0.72; p = 0.02) and total stress (r = -0.74, p = 0.01) (RESTQ). Additionally, in males only, the strain was correlated positively with RESTQ recovery-stress balance (r = 0.69; p = 0.03), and negatively correlated with general stress (r = -0.81, p = 0.01), and sport stress (r = -0.89, p < 0.01). No correlations between HRV, RHR, strain or recovery, and stress variables were observed in females. Associations between wearable technology measures of HRV, RHR, strain, and recovery with validated measures of ED and psychological stress should continue to be explored with a focus on underlying mechanisms and moderating influences of biological sex.